The Effects of Mergers and Acquisitions on Company’s Operating Performance - Xiaoying, Pan (2013)
This paper examines the effects of mergers and acquisitions on the firm’s operating performances in UK from 2005-2008. The performances of acquiring firms are compared with the control group of non-merging firms by employing a fixed-effect model. Four performances measurements are employed including ROA, ROCE, profit margin and cash flow ratio. There is no significant evidence that mergers and acquisitions have impact on company’s operating performance over the whole sample. However, significant positive effects of M&A are found in particular financial year and in certain industries.